Are the preference and selection patterns of hermit crabs for gastropod shells species- or site-specific? - Dominciano, L. C. C.; Sant'Anna, B. S. [UNESP]; Turra, A. (Elsevier B.V., 2009)
Experimental analyses of hermit crabs and their preferences for shells are essential to understand the intrinsic relationship of the crabs' dependence on shells, and may be useful to explain their shell use pattern in nature. The aim of this study was to evaluate the effect of crab species and site on the pattern of shell use, selection, and preference in the south-western Atlantic hermit crabs Pagurus brevidactylus and Pagurus criniticornis, comparing sympatric and allopatric populations. Differently from the traditional approach to evaluate shell preference by simply determining the shell selection pattern (i.e., the number of shells of each type selected), preference was defined (according to [Liszka, D., Underwood, AJ., 1990. An experimental design to determine preferences for gastropod shells by a hermit-crab. J. Exp. Mar. Biol. Ecol., 137(1), 47-62]) by the comparison of the number of crabs changing for a particular shell type when three options were given (Cerithium atratum, Morula nodulosa, and Tegula viridula) with the number of crabs changing for this same type when only this type was offered. The effect of crab species was tested at Cabelo Gordo Beach, where P. brevidacrylus was found occupying shells of C. atratum, M. nodulosa, and T viridula in similar frequencies, whereas P. criniticornis occupied predominantly shells of C atratum. In laboratory experiments the selection patterns of the two hermit-crab species for these three gastropods were different, with P criniticornis selecting mainly shells of C atratum, and R brevidactylus selecting more shells of M. nodulosa. The shell preference was also dependent on crab species, with P. criniticornis showing a clear preference for shells of C atratum, whereas P. brevidactylus did not show a preference for any of the tested shells. The effect of site was tested for the two species comparing data from Cabelo Gordo to Preta (P brevidactylus) and Araca beaches (P. criniticornis). The pattern of shell use, selection, and preference was demonstrated to be dependent on site only for P. brevidactylus. The results also showed that the shell use pattern of P criniticornis can be explained by its preference at both sites, whereas for P. brevidactylus it occurred only at Cabelo Gordo, where the absence of preference was correlated with the similar use of the three gastropod species studied. Finally, the results showed that the shell selection pattern cannot be considered as a measure of shell preference, since it overestimates crab selectivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Hermit crab; Pagurus brevidactylus; Pagurus criniticornis; Shell preference; Shell utilization